Pendampingan Pembuatan Perangkat Pembelajaran Berbasis Alat Peraga Untuk Meningkatkan Kualitas Pembelajaran Matematika - Zulmi Restika Rini; Yoannes Romando Sipayung; Lisa Virdinarti Putra (Jurnal Pengabdian Masyarakat (abdira), 2021)
Learning always develops all the competencies possessed in order to be able to carry out learning that makes students active. One of the lessons that can be used is learning to use teaching aids. The phenomenon in the field shows that most of the learning has not used teaching aids. In fact, teaching through teaching aids can improve understanding of concepts and find the formulas needed to solve problems. One of the reasons is the unavailability of adequate mathematics teaching aids. As a result, the results of learning mathematics have not been maximized. Based on this thinking, students need to be assisted in order to achieve maximum mathematics learning outcomes. One of the efforts that can help students is through assistance in making teaching aids. Methods of carrying out activities include: brief explanations of teaching aids, training and guiding students to make teaching aids, simulations using teaching aids in understanding mathematical concepts and formulas. The results of the mentoring showed positive student responses to the activities, students were able to make teaching aids from surrounding materials, students were able to use teaching aids to understand mathematical concepts and formulas.